Peranan Pemerintah Daerah Dalam Pembangunan Pertanian Berbasis Green Economy (Studi Pada Dinas Pertanian Kota Kediri) - Bukhorida, Novy Faradella (Jurnal Administrasi Publik, 2015)
Abstact: The Role of Local Government in the Agricultural Development Based on Green Economy (Study Case of Dinas Pertanian Kota Kediri). Indonesia has long been known as a country with vast agricultural sector and have an important role in the economy and a long history. This is because Indonesia is supported by the potential and natural resources suitable for the development of agriculture such as tropical climate that supports the plant to thrive. Agriculture's contribution to development is closely related to the running of green economy, which in the context of economic development it is not only the physical and social progress are taken into account, but also aspects of ecological sustainability. The concept of green economy for agriculture is not just a process to save the earth from destruction, but also bring great mission, that of calling people to care about the environment. The role of the Department of Agriculture Kediri in this case is needed so that people especially farmers became aware that the preservation of nature in the process of agricultural development is very important because the nature is a place we live and where we live. Keywords: agricultural development, green economy Abstrak: Peranan Pemerintah Daerah Dalam Pembangunan Pertanian Berbasis Green Economy (Studi Pada Dinas Pertanian Kota Kediri). Indonesia sudah sejak lama dikenal sebagai negara dengan sektor agrarisnya yang luas dan memiliki peran penting dalam perekonomian dan sejarah yang panjang. Hal ini disebabkan karena Indonesia di dukung oleh potensi dan sumber daya alam yang cocok untuk pengembangan bidang pertanian seperti iklim tropis yang mendukung tanaman untuk tumbuh subur. Kontribusi pertanian terhadap pembangunan erat kaitannya dalam menjalankan green economy, dimana dalam konteks pembangunan ekonomi maka bukan hanya kemajuan fisik dan sosial saja yang dipertimbangkan tetapi juga aspek keberlanjutan ekologis. Konsep dari green economy untuk pertanian bukan hanya sekedar proses untuk menyelamatkan bumi dari kehancuran, tetapi juga membawa misi besar, yaitu menyadarkan manusia agar perduli dengan lingkungan. Peranan Dinas Pertanian Kota Kediri dalam hal ini sangat dibutuhkan agar masyarakat terutama petani menjadi sadar bahwa menjaga kelestarian alam dalam proses pembangunan pertanian sangat penting karena alam tempat kita tinggal dan tempat kita hidup. Â  Kata kunci: pembangunan pertanian, green economy